Penyakit Blas Pyricularia grisea pada Tanaman Padi dan Strategi Pengendaliannya - Sudir Sudir; A. Nasution; Santoso Santoso; B. Nuryanto (Iptek Tanaman Pangan, 2014)
Blast disease caused by Pyricularia grisea, is one of the major rice disease constraining rice productivity in Indonesia. The disease formerly was found on the upland rice, but lately it became an important disease on the wetland rice in West Java, Central Java, and East Java. The shift of disease ecology was possibly due to the emergence of new races of the fungus, which became adaptive to the wetland, coupled with the high rate of N fertilizer and the non-resistance varieties planted by farmers. The disease epidemic is influenced by many factors, including macro and micro climates (season, temperature and humidity), cultivation technique, and rice varieties. Yield reduction due to the disease varied from light to heavy (100%), depending on the disease intensity. The recommended control technique is by way of integrated disease control, integrating cultivation techniques, resistant varieties, and fungicide sprays when necessary. Planting resistant varieties is the most economic, but the resistance is fastly broken over seasons and areas due to the existence of many races. Planting resistant varieties, therefore, should be supported by other control techniques. Choice of varieties containing resistant gene(s) matches with the pathogen race in the field is recommended. It is important, therefore, to monitor the composition of races in the area.